The state, development planning and liberalisation in India - Byres, T. J. (Delhi ; New York : Oxford University Press, 1997)
The original volume upon which this book is based - The State and Development Planning in India (OUP, 1994) - is a landmark in the political economy literature on post-1947 India. It sought to provide a comprehensive treatment of the nature, achievements and limitations of Indian development planning between 1950 and the late 1980s. With papers by some of India's outstanding political economists, this volume addresses issues which continue to be relevant in India's present liberalised environment. Students of economics and political science and other interested readers will find that this book facilitates an informed assessment of India's current development strategy.
10. Planning and Foreign Investment in Indian Manufacturing / Nirmal Kumar Chandra.
Originally published: The state and development planning in India. Delhi ; New York : Oxford University Press, 1994.
Includes bibliographical references and indexes.
Keywords: Social classes -- India; Investments, Foreign -- India; India -- Economic policy -- 1980-; India -- Social policy